1990
DOI: 10.1016/0168-1176(90)80006-o
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the ion stability on the fate of intermediate ion/neutral complexes

Abstract: Carbonyl protonated aromatic ketones a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Furthermore the mechanism in Scheme 14 implies that the branching between ester elimination and acyl cation formation should depend on the (relative) stability of the acyl cation. This is supported by the experimental results [38]. Table 1 shows the MIKE spectra of a series of 4-methoxymethyl-substituted phenones, originally protonated at the carbonyl group.…”
Section: Intermediate Ion/neutral Complexessupporting
confidence: 67%
See 2 more Smart Citations
“…Furthermore the mechanism in Scheme 14 implies that the branching between ester elimination and acyl cation formation should depend on the (relative) stability of the acyl cation. This is supported by the experimental results [38]. Table 1 shows the MIKE spectra of a series of 4-methoxymethyl-substituted phenones, originally protonated at the carbonyl group.…”
Section: Intermediate Ion/neutral Complexessupporting
confidence: 67%
“…The explanation for this effect is a barrier to the "ring-walk" migration of the proton around the naphthalene system imposed by the ring junction. This has been supported by MNDO calculations of the heat of formation of the relevant protomers [38]. Analogously, it is difficult for a proton to cross by successive 1,2-shifts from one benzene ring to the other in the diphenyl and terphenyl systems, as depicted in Scheme 15, because of the energetically unfavourable ipso protomers.…”
Section: Intermediate Ion/neutral Complexesmentioning
confidence: 72%
See 1 more Smart Citation
“…And the mobile proton model13–18 which describes the mobility of the proton across the protonated molecule is proposed and applied not only to the flexible peptides and proteins but also to the rigid molecules. In fact, the mobile characteristic of proton was first observed and unambiguously characterized by Grutzmacher and co‐workers 19–24. Take naphthalene with a carbonyl group on one end and a methoxymethyl on the other for example,21 they observed that the ionizing proton which is definitely attached to the carbonyl oxygen migrates across the ring to the oxygen atom of the methoxy group, leading to the elimination of methanol.…”
Section: Introductionmentioning
confidence: 95%
“…In fact, it has been shown [7] by varying the acyl substituent RCO, that the fragmentation by the internal ion-neutral reaction occurs only as long as the direct dissociation is not favored by yielding an especially stable acyl cation RCO+. Another interesting modification of this model system is a change of the benzene nucleus by a larger aromatic group.…”
mentioning
confidence: 99%